Factors Determining Smallholder Farmers to Upscale their Cattle Business - Restiyana Agustine; Mujtahidah Anggriani Ummul Muzayyanah; Ahmad Romadhoni Surya Putra; Endang Baliarti (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2023)
The maintenance of beef cattle in Indonesia is mainly carried out by smallholder farmers, so to meet national demand, the beef cattle population needs to increase. While the government-initiated programs to increase e cattle population are many, studies to analyze smallholder farmers’ interest in improving their cattle size remain limited. This study aims to analyze factors influencing the interests of smallholder farmers in improving their beef cattle business. The variables were farmers’ age, gender, education level, family size, land ownership, beef cattle ownership, monthly income level, and cattle breed. The potential obstacles farmers faced to increasing their beef cattle business were investigated. Conducted in Blora, Grobogan, Kebumen, Klaten, and Rembang Regencies, Central Java Province, this study purposively selected 287 beef cattle farmers aged 15-24 years as study respondents. The collected data were then subjected to binary logistic regression analysis using Stata 16. The findings showed that farmers’ motivation to increase the population of cattle they raised was influenced by their age and monthly income. The older the farmers, the less probable they were interested in improving their business. Farmers earning >IDR 1,000,000.00-3,000,000.00 per month showed a probability of interest in increasing their business by growing the beef cattle population.